Raising Children in Single-Parent Families - Westrupp, Elizabeth Mary; Lucas, Nina; Abela, A; D'Esposito, Fabrizio; Nicholson, Jan Maree (John Wiley & Sons, 2013)
Children from single-parent families fare more poorly on multiple outcomes than those in two-parent families. Most explanations for these differences assume that compromised parenting and parent mental health play a central role. This chapter explores the contribution of a range of factors to the parenting and mental health of single mothers using data from approximately 1000 Australian single mothers with a child aged 4–5 or 8–9 years. The findings show that single mothers are more likely than couple mothers to experience parenting and mental health difficulties; however, they also face heightened adversity in their home and extra-familial environments. Importantly, this comparison of single and couple mothers facing similar levels of adversity shows no difference in poor parenting practices, although single mothers remain more vulnerable to psychological distress. These findings have policy implications since they challenge the prevailing view that single-parent families inherently provide sub-optimal environments for raising children.
Contemporary Issues in Family Studies: Global Perspectives on Partnerships, Parenting and Support in a Changing World
Keywords: Health -- Mental; Children -- Outcomes; Families -- Lone parents; Families and relationships; Health and wellbeing; Families; Health; Children; Mental; Outcomes; Lone parents; Families and relationships; Health and wellbeing